Social Media Marketing, Brand Image, Brand Awareness, Perceived Quality And Purchase Intention In Skincare Product Users - Oktavia, Kiki Nur; Mariam, Siti (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to examine the influence of social media marketing on brand image, brand awareness, and perceived quality in skincare product users. Research methods using quantitative approach descriptive causality. The sample consisted of 105 respondents who are active skincare users on instagram. Data were collected through online questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that social media marketing has a significant and positive influence on brand image, brand awareness, and perceived quality, which can increase purchase intention. These findings indicate that an increase in social media marketing can increase consumer purchase intention. Based on the results of this study, it is recommended that skincare companies are advised to continue to optimize social media marketing strategies to build a positive brand image, increase brand awareness, and strengthen perceived quality in order to create consumer desire to buy products.